2020
DOI: 10.1186/s13104-020-4935-3
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 8 infection may contribute to oxidative stress in diabetes type 2 patients

Abstract: Objective: To investigate the link between Human Herpesvirus 8 (HHV8) infection and plasma oxidative stress in patients with diabetes mellitus type 2 (DM2). Results: Blood samples collected from DM2 and control subjects were screened for the presence of antibodies against HHV8 and for biomarkers of oxidative stress. We determined the products of radical damage on the plasma lipid fraction, such as malondialdehyde (MDA), fatty acid hydroperoxides (HP) and 7-ketocholesterol (7-keto), the oxidation products of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Although HHV8 can cause frequent and severe sarcoma or other lympho-proliferating diseases in immune-depressed subjects, it is generally constrained to the latent phase in order to escape adaptive immunity. It has also been reported that HHV8 together with the activation of both humoral and cellular immunity, as well as the induction of cytokines and reactive oxygen species (ROS), induces persistent metabolic modifications in the infected endothelial cells [60,66,[74][75][76][77][78]. Recently, Angius et al [24] corroborated previous evidence [63,65] and also found that the anti-HHV8 immune response can further enhance the uptake of both glucose and insulin in latently infected endothelial cells, strengthening the hypothesis that anti-HHV8 antibodies provide additional support for virus persistence in the host [24].…”
Section: Immune Response and Cell Metabolismmentioning
confidence: 99%
See 4 more Smart Citations
“…Although HHV8 can cause frequent and severe sarcoma or other lympho-proliferating diseases in immune-depressed subjects, it is generally constrained to the latent phase in order to escape adaptive immunity. It has also been reported that HHV8 together with the activation of both humoral and cellular immunity, as well as the induction of cytokines and reactive oxygen species (ROS), induces persistent metabolic modifications in the infected endothelial cells [60,66,[74][75][76][77][78]. Recently, Angius et al [24] corroborated previous evidence [63,65] and also found that the anti-HHV8 immune response can further enhance the uptake of both glucose and insulin in latently infected endothelial cells, strengthening the hypothesis that anti-HHV8 antibodies provide additional support for virus persistence in the host [24].…”
Section: Immune Response and Cell Metabolismmentioning
confidence: 99%
“…Moreover, the dysfunction of endothelial cells has been involved in the pathophysiology of metabolic diseases and DMT2 [90,91], and endothelial dysfunction is believed to contribute to the clinical expression of atherosclerosis and other complications of diabetes [92]. Overall, several findings have led to the hypothesis that HHV8 could be implicated in inducing some metabolic alterations, such as the increase of insulin binding and glucose uptake, which may be the initial event for activating the metabolic syndrome and diabetes [60,77,78,81,82,89,93]. It is commonly accepted that insulin hyper-secretion is considered a triggering cause of diabetes, and the discovery of the causes that are linked to insulin hyper-secretion is fundamental in the design of specific diabetes treatment [94,95].…”
Section: Hhv8 Prevalence In Chronic Diseasesmentioning
confidence: 99%
See 3 more Smart Citations